Seedling resistance of some bread wheat genotypes to Fusarium pseudograminearum - Yazici Kuzu, Eda; Karakaya, Aziz; Erginbas-Orakci, Gul; Dababat, Abdelfattah A.; Aydogan, Sinan (Plant Protection Bulletin, 2022)
Fusarium pseudograminearum is one of the most damaging Fusarium species that causes root, crown, and foot rots in wheat. Identification of resistant germplasm is one of the most efficient and environmentally sound control methods. However, up to date, limited wheat genotypes with partial resistance are available. Therefore, in this study, the seedling resistance reaction of 200 bread wheat genotypes plus 6 control genotypes obtained from CIMMYT to Fusarium pseudograminearum was determined under growth room conditions. Out of the 200 tested genotypes; 1 (0.5%), 35 (17.5%), 112 (56%), 45 (22.5%), and 7 (3.5%) were resistant, moderately resistant, moderately susceptible, susceptible and very susceptible to Fusarium pseudograminearum, respectively. Resistant and moderately resistant genotypes could be used in breeding studies for developing crown rot-resistant cultivars.